How well has the National Climate Budget supported the 2011-2028 National Climate Change Action Plan? (or, why a Task Force El Nino?) - Toby C. Monsod (University of the Philippines, School of Economics (UPSE), 2024)
The paper explores how well the National Climate Budget (NCB), starting in 2016, has supported the climate reform agenda articulated in the National Climate Change Action Plan 2011-2028 (NCCAP), now on its 14th year. It observes that the NCB, as appropriated, grew from P175 billion in 2016 to P457.4 billion in 2024, or by 161%, with a sharp increase of P174.8 billion, or 60.3%, occurring between 2022 and 2023. However, the sharp increase in 2023 is accounted for by just two agencies - DPWH and DOTR - whose incremental climate budgets account for 98% of the increase, or P146 billion and P24 billion respectively. Moreover, the share of NCB in the primary budget was only 7.3% on average over the period, and never higher than 10% in any one year, raising doubts about a "whole-of-government" approach to addressing climate change risks and impacts. Among the seven NCCAP strategic priorities, Water Suffciency accounts for the greatest share at an average of 63.9% of the climate budget every year. Yet recurring El Nino events, which are known to exacerbate water scarcity, continue to require the activation of an ad-hoc mechanism to "ensure the country's readiness to fght the effects of the El Nino phenomenon". A deeper dive into the items for Water Suffciency indicates a budget that is almost totally allocated to food control and other construction works of DPWH; allocations to strengthen the regulatory environment and better manage the supply and demand of water resources are negligible in comparison. Prospects for advancing water security and mitigating El Nino impacts are discussed.
Keywords: 330; Klimaschutz; Klimapolitik; Öffentlicher Haushalt; Öffentliche Ausgaben; Philippinen